2017
DOI: 10.4103/2321-0656.193996
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and predictors of cognitive impairment in type 2 diabetic population of Punjab, India

Abstract: Background: The present cross sectional study was carried out on 516 subjects with type 2 diabetes from a tertiary health care hospital to identify the prevalence and predictors of cognitive impairment in diabetes. Materials and Methods: Cognitive impairment was tested using Mini Mental Scale Examination (MMSE), Trail making tests-A and B (TMT-A and TMT-B). Efficiency of these tests to diagnose cognitive impairment was analysed using reliability index (Cronbach's α = 0.82), which ruled out any intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 39 publications
2
22
3
Order By: Relevance
“…Internal consistency of the questionnaire was reported to be 0.82. [ 18 ] MMSE had been standardized for our research by forward translation, expert panel back translation, pretesting and cognitive interviewing and concluded with the preparation of final version. Based on the scores obtained, they were classified into normal (score 25–30) and mild cognitive impairment (score <25).…”
Section: Ethodologymentioning
confidence: 99%
“…Internal consistency of the questionnaire was reported to be 0.82. [ 18 ] MMSE had been standardized for our research by forward translation, expert panel back translation, pretesting and cognitive interviewing and concluded with the preparation of final version. Based on the scores obtained, they were classified into normal (score 25–30) and mild cognitive impairment (score <25).…”
Section: Ethodologymentioning
confidence: 99%
“…Few studies have verified that type 2 diabetes is a biological risk factor of cognitive impairment. [13][14][15][16] In contrast, cardiovascular diseases such as stroke have been identified as critical diseases that can lead to neurocognitive dysfunction in various areas, including attention, executive function, language, and memory. [17][18][19] A longitudinal study identified changes in cognitive function over 3 years in 630 patients after their first stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have identified the relationship between alcohol consumption and cognitive decline. 16 In particular, a follow-up longitudinal study of 6542 middle-aged adults found that alcohol use disorder can predict memory impairment. 25 However, the association between smoking and cognitive decline remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from across the world have shown the association between NCDs and the decline of cognitive function leading to mild cognitive impairment (MCI) or dementia. 11 12 13 14 However, the etiological pathway of this relationship is not known. MCI is the transitional phase between the normal aging process and dementia.…”
Section: Introductionmentioning
confidence: 99%